2009
DOI: 10.1039/b816603j
|View full text |Cite
|
Sign up to set email alerts
|

Cell up-take control of gold nanoparticles functionalized with a thermoresponsive polymer

Abstract: Surface decoration of gold nanoparticles with thermoresponsive polymers endows a temperature tunable colloidal system switchable for enhanced intracellular up-take. Gold nanoparticles (AuNP, 18 ± 11 nm-diameter) produced by laser ablation synthesis in liquid solution were surface coated with thermoresponsive thiol terminated poly-N-isopropylacrylamide-co-acrylamide co-polymer possessing a lower critical solution temperature (LCST) at 37 °C. Under selected conditions about 3800 polymer chains were conjugated pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 61 publications
3
98
1
Order By: Relevance
“…The interaction of unstable nanoparticles with biomolecules probably leads to the particle agglomeration and their concentration in the liver. Similar nonfunctionalized 18-nm AuNPs and the particles coated also with polyacrylamide displayed no cytotoxicity to human breast adenocarcinoma cells [11]. No cytotoxic effect was also reported for smaller 10-nm unmodified AuNPs towards dendritic cells by Villiers et al [12].…”
Section: Particle (Stabilizer) Surface Effectmentioning
confidence: 67%
“…The interaction of unstable nanoparticles with biomolecules probably leads to the particle agglomeration and their concentration in the liver. Similar nonfunctionalized 18-nm AuNPs and the particles coated also with polyacrylamide displayed no cytotoxicity to human breast adenocarcinoma cells [11]. No cytotoxic effect was also reported for smaller 10-nm unmodified AuNPs towards dendritic cells by Villiers et al [12].…”
Section: Particle (Stabilizer) Surface Effectmentioning
confidence: 67%
“…Such effects can be nicely exemplified when comparing, for instance, the influence of ligands on internalisation. While primary ligand-free AuNPs entered the cells by an unknown non-endosomal uptake mechanism (Salmaso et al 2009, AuNPs with ordered arrangements of hydrophilic and hydrophobic functional groups were internalised by membrane wrapping (Verma et al 2008), and AuNP with citrate ligands underwent endocytosis (Shukla et al 2000).…”
Section: Delivering the Nanogold Label: Cellular Internalisation Of Amentioning
confidence: 99%
“…This aggregation strongly increased the scattering of light, with a color different from that scattered from the original Apt-AuNPs and cell organelles. Salmaso et al [31] reported on AuNPs that were surface-coated with thermoresponsive thiol-terminated poly-N-isopropylacrylamide-co-acrylamide copolymer. The cell uptake of polymer-coated AuNPs can be temperature-controlled; this opens new perspectives for in vivo testing aimed at thermally controlled targeting of tumors or inflamed tissues.…”
Section: Metallic Nanoparticlesmentioning
confidence: 99%
“…Here, we review a few immobilization processes and show the reaction paths for a better understanding of biomolecule immobilization systems. [31] 3.1.1 Synthesis of PNIPAm-co-Am-SH. PNIPAm-co-Am-COOH (97.3 mg, 16.2 µmol) was dissolved in 0.75 ml of anhydrous DMSO and N-hydroxysuccinimide (HOSu) (19.7 mg, 171 µmol) and dicyclohexylcarbodiimide (DCC) (29 mg, 140.7 µmol) were added (figure 1).…”
Section: Biomolecule Immobilizationmentioning
confidence: 99%